Belanja Tanpa Rencana: Peran Kontrol Diri dan Electronic Word Of Mouth dalam Pembelian Impulsif Mahasiswa - Nanda Dian Kartika; Lania Muharsih; Yulyanti Minarsih (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the influence of self-control and electronic word of mouth (e-WOM) on impulsive buying among university students in Karawang. The research employed a quantitative approach with a causal design and involved 206 students aged 18–25, selected through purposive sampling. Instruments used included impulsive buying scales, Brief self-control scales and e-WOM scales. analyzed using multiple linear regression. The results showed that self-control had a significant negative effect, while e-WOM had a significant positive effect on impulsive buying (p < 0.05). Although most respondents had high self-control (46.1%), many still exhibited high levels of impulsive buying (34.5%). This indicates that self-control does not always effectively suppress the influence of e-WOM. The novelty of this study lies in identifying the mismatch between high self-control and impulsive behavior. The findings imply the need for digital education and stronger self-regulation in online shopping environments, especially among students exposed to e-WOM and impulsive buying tendencies.